Linking shelter conditions to health: A multisystem analysis of stress, metabolism, and fecal microbiota in dogs - Adul Saengthong; Janine L. Brown; Patcharapa Towiboon; Khanittha Punturee; Songphon Buddhasiri; Korakot Nganvongpanit; Veerasak Punyapornwithaya; Wuithipong Tocharoennirattisai; Jaruwan Khonmee (PLoS ONE, 2026)
Variations in space allocation and husbandry practices can significantly affect the health and welfare of long-term shelter dogs. This study compared adrenal, metabolic, and microbiological health indicators among dogs from three shelters in Thailand: Shelter A – low-density (20.3 m²/dog), adequate enclosure size (101.9 m²), and an enrichment program; Shelter B – medium-density (3.9 m²), large enclosures (150 m²); and Shelter C – high density (3.0 m²), one communal space (800 m²), and no enrichment. Fecal glucocorticoid metabolite (fGCM) concentrations, oxidative stress (malondialdehyde, MDA), metabolic parameters (glucose, insulin, fructosamine, lipid profiles), and fecal microbiota composition and diversity were measured and analyzed in relation to management factors. Dogs in Shelter A exhibited the lowest fGCM concentrations (207.41 ± 4.55 ng/g), normal metabolic profiles, and richer, more even fecal microbiota. In contrast, dogs in Shelter C, a temple-based facility with more crowding and limited space, exhibited higher fGCM (278.71 ± 10.44 ng/g) and fructosamine concentrations, reduced alpha diversity, and a highly skewed Firmicutes-to-Bacteroidota ratio, suggesting possible adrenal cortical and microbial dysbiosis. Shelter B presented intermediate values across most parameters and management inputs. These findings show that management practices, including space allocation and enrichment, can influence stress physiology, metabolic health, and fecal microbiota composition in long-term sheltered dogs.